1998
DOI: 10.1590/s0100-879x1998001000004
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in patients with sickle cell anemia or sickle cell trait

Abstract: Patients with sickle cell anemia (Hb SS) or sickle cell trait (Hb AS) may present several types of renal dysfunction; however, comparison of the prevalence of these abnormalities between these two groups and correlation with the duration of disease in a large number of patients have not been thoroughly investigated. In a cross-sectional study using immunoenzymometric assays to measure tubular proteinuria, microalbuminuria, measurement of creatinine clearance, urinary osmolality and analysis of urine sediment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
(15 reference statements)
7
35
3
Order By: Relevance
“…3,6,7,10,11 The rare renal medullary carcinoma is seen almost exclusively among HbAS patients. 6,11,12 In epidemiologic studies, the presence of HbAS has been associated with microalbuminuria and proteinuria, particularly among diabetic men, 13,14 and African Americans with autosomal dominant polycystic kidney disease (AD-PKD) and HbAS have been shown to progress to ESRD more rapidly than those without the trait. 15 With its associated structural and physiologic changes, HbAS could adversely affect renal function, especially in the setting of comorbid disease, and may represent a potential risk factor for kidney disease.…”
mentioning
confidence: 99%
“…3,6,7,10,11 The rare renal medullary carcinoma is seen almost exclusively among HbAS patients. 6,11,12 In epidemiologic studies, the presence of HbAS has been associated with microalbuminuria and proteinuria, particularly among diabetic men, 13,14 and African Americans with autosomal dominant polycystic kidney disease (AD-PKD) and HbAS have been shown to progress to ESRD more rapidly than those without the trait. 15 With its associated structural and physiologic changes, HbAS could adversely affect renal function, especially in the setting of comorbid disease, and may represent a potential risk factor for kidney disease.…”
mentioning
confidence: 99%
“…The first study that linked hyposthenuria and nocturnal enuresis was in 1967 by Noll et al [43]. This assumption was based on the fact that failure to concentrate urine is one of the earliest infarction-related renal complication of SCA [44].…”
Section: Enuresis In Sca: the Postulated Etiologymentioning
confidence: 99%
“…Enuresis and nocturia, as indicators of UBD, are common in individuals with sickle cell anemia [18,43,53,54]. Field et al reported that enuresis declined with age but nocturia persisted throughout childhood and early adulthood [18].…”
Section: The Urinary Bladder and Nocturnal Enuresismentioning
confidence: 99%
“…The pathophysiology of renal damage and proteinuria in this population is unclear [9]. The proposed process involves ischemia and microinfarction resulting from medullary hypoxia, acidosis, and hyperosmolarity, an environment that promotes red blood cell (RBC) sickling.…”
Section: Renal Disease In Sickle Cell Anemia Patientsmentioning
confidence: 99%